Eduardo Galeano nas tramas do discurso: a reconstituição da memória como forma de (re)existência - Aquino, Luana Vargas (2023)
In this study, we propose, based on the theoretical constructs of Discourse Analysis, to explain what resonates in Eduardo Galeano’s writing process in his relationship with Latin America. Thus, we understand Galeano’s place as an adventurous subject, who ventures into places, stories, people, who lives on a tightrope between present, past and future – a story hunter –. coming from a land where one does not witness the “wild childhood of capitalism, but its decrepitude”, land this victim of a system “moribund since birth” (GALEANO, [1971]2020, p. 324). It is from the notion of subject, as developed by Pêcheux ([1975]1995), that we walk in the analytical process, observing how this Latin American subject is constituted in the face of the production conditions that are imposed on him. We are interested in the positions taken, the displacements and slips that constitute a subject crossed by language and ideologically questioned. Still, the notion of interdiscourse (PÊCHEUX, [1975]1995; ORLANDI [1999]2015) guides this writing, so that it is through this concept that we understand how the already-said return in the utterance of a subject. The Latin America that we bring to compose our analyzes is the one described by Galeano in his work; an America with open veins, about to overflow (senses, memories, effects...). This space, which comprises a vast territorial extension, occupies a place of production of meanings in the constitution of the subject, relating to the structures and processes that are part of this constitution. Still, we will deal with some fundamental notions of AD that are articulated to think about our object of analysis, such as the functioning of production conditions, ideological, discursive and imaginary formations and other concepts that come from them and are intertwined in this research. We aim, through writing, to build an adventure experience in front of our Research corpus, to make Galeano’s story explicit in order to tell the history of Latin America, having as a guide the incessant reminder of seeing the big story through the small story. We start just like an archaeologist, who, through the fragments, enters the quest – eternal and impossible, to find unity. We know, as discourse analysts, that unity is an illusion, on the other hand, seeking it is what guarantees our unique movement in the face of the corpus. In this sense, the work of selecting, gathering and grouping excerpts from books, interviews and other artistic-symbolic materials is already established as a movement of appropriation of the corpus. Finally, it is through the encounter of the corpus of research with the analytical device built in this research, that we weave the hypothesis that Galeano produces a space of (re)existence from writing, in a process of reconstitution of the memory of Latin America.